An accurate map of North America describing and distinguishing the British and Spanish dominions of this great continent according to the definitive treaty concluded at Paris 10th Feby. 1763 : also all the West India Islands belonging to and possessed by the several European princes and states - Bowen, Emanuel, d. 1767 (Printed for Robert Sayer, 1775)
Map shows European settlements, areas of Native American habitation, routes of Spanish galleon voyages in the Gulf of Mexico and the Caribbean. Includes explanation to symbols, text of Articles 4-7, 9, 17-18, and 20 of the Treaty of Paris, 1763, textual commentary and notes on explorers and discovery dates, and illustrated title cartouche depicting new world natives and animals. Insets: "A particular map of Baffin and Hudson's Bay" and "The passage by land to California discovered by Father Eusebius Francis Kino." Scale not given.